Intelligent Building Health Monitoring and Assessment - Xin, Jingzhou; Jiang, Yan; Wu, Bo; Yang, Simon X. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Buildings play an indispensable role in urban development. As typical structures of transportation buildings, bridges serve as crucial nodes in connecting different regions, promoting economic growth, and ensuring social security. However, with the extension of their service life, the performance of bridges will inevitably decline. Performance monitoring and evaluation are crucial during the life cycle of bridges. The accelerating convergence of civil engineering, materials science, and artificial intelligence has sparked the interest of researchers from different disciplines in the emerging field of bridge state perception. This reprint covers topics on condition monitoring and assessment of engineering structures, featuring 13 papers. These studies provide some novel methods, models, and technological applications for bridge condition perception, which are of great significance for the design, construction, and assessment of bridges.